PENILAIAN KINERJA KARYAWAN MELALUI SPIRITUAL LEADERSHIP, NORMATIVE COMMITMENT DAN ETIKA KERJA ISLAMI - Natoil Natoil (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. The purpose of this research is to test the influences of spiritual leadership, Islamic work ethic, and normative commitment, on employee performance moderated by work monitoring. Using these variables, the usage of these variables are able to solve the arising problem within employees KSPPS Kabupaten Semarang. Statement of this problem is how increase employee performance?. The samples size of this research is 106employees KSPPS Kabupaten Semarang. Using the Statistical Package Social Science (SPSS). The results show that spiritual leadership, Islamic work ethic, and normative commitment on employee performance moderated by work monitoring. The effect of spiritual leadership on employee performance are significant; The effect of Islamic work ethic on employee performance are significant; normative commitment on employee performance are significant; The effect of Islamic work ethic on employee performance moderated by work monitoring are significant; and The effect of normative commitment on employee performance moderated by work monitoring are significant.